V. 2 - Seervai, H.M. (Delhi, 2015)
This book... is the best book for lawyers on the Indian Constitution yet published... the articles of the Constitution and provisions of relevant statutes are comprehensively discussed, more than half the commentary being devoted to the fundamental rights and remedies for their violation... His criticisms are invariably constructive and, where necessary, he has suggested constitutional amendments... No other author has analysed the case-law with the care and clarity so prominent in this book. The canons of construction impeccably set out in the second chapter are relentlessly applied to questionable decisions. Clearly there are important decisions which need reconsideration. The author emphases that... a fruitful source of error is the use of semi-religious terminology... (which) in part explains the amazing decision in Golak Nath's case that a constitutional amendment must conform to the fundamental rights, so that a fundamental right cannot be amended... the author rewrote his last chapter, dealing at length with this case and giving cogent reasons for his view that this decision is productive of great public mischief and should be overruled... This book will run to many editions.
Keywords: Constitutional law